Walking Workers systems: a sequence analysis for flexible mixed model lines. Issue 1 (2021) - Bortolini, M.; Faccio, M.; Galizia, F.G.; Gamberi, M.; Pilati, F.
Abstract: The Walking Workers (WW) systems are interesting for their flexibility attributes, especially in terms of ability to manage the product variety and market demand. This paper aims to study the mixed model sequencing problem considering un-paced, unbuffered WW systems. The authors propose an original algorithm, called "accordion algorithm" for the models sequence definition and the makespan minimization. This algorithm is tested and validated through a simulative study highlighting the influence of the task time variations and of the resources number on the system performances.